Iridofundal Coloboma Associated with Vitreous Haemorrhage and an Intraocular Mass: A Case Report - Sodhi, Punita Kumari; Sharma, Anu; Verma, Saurabh; Shaw, Ekta (Nepalese Journal of Ophthalmology, 2022)
Introduction: Iridofundal colobomas, being developmental defects, are known to be accompanied by several ocular anomalies but an association with vitreous hemorrhage and an intraocular mass has not been reported earlier.Case: We report a case of an 18 years old subject having iridofundal coloboma in both eyes and an association of vitreous hemorrhage and an intraocular mass in the left eye. The diagnosis was confirmed with a detailed ocular examination, fundus fluorescein angiography, swept-source optical coherence tomography and ultrasonography. The laser barrage of coloboma caused a regression in the size of the intraocular mass and prevented recurrence of vitreous hemorrhage over one and half years of follow-up.Conclusion: The source of vitreous hemorrhage in this subject is unclear though some anomalous vessels in relation to the supero-nasal mass, optic disc and coloboma of the left eye might have caused it. The laser barrage of coloboma obscured these anomalous vessels resulting in the regression of the intraocular mass.